ANALISIS PENGARUH SUMBER DAYA MANUSIA, PARTISIPASI PENYUSUNAN ANGGARAN, DAN PENYUSUNAN ANGGARAN TERHADAP SISTEM MANAJEMEN AKUNTANSI PENGELOLAAN KEUANGAN DESA MELALUI BMPD TIMOR TENGAH SELATAN - Se'u, Dedy Raidons; Djawang, Jofret Umbu Soru Peku (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
Research is focused to analyze the influence of human resources, participation in the preparation of the budget, and the preparation of the budget Toward Financial Management Accounting Management system of village in South Central Timor Regency, East Nusa Tenggara province. This research was conducted because the village Government apparatus in the financial management of the village has not been in accordance with the applicable provisions. This research is expected to be beneficial to the Government of the village of South Central Timor Regency province of East Nusa Tenggara (NTT) in an attempt to improve the financial management of the village is effectively and efficiently in order to improve the performance of the apparatus of Government village in South Central Timor Regency. Research conducted in six villages that existed in South Central Timor Regency implementing financial management as the location of the village. Data sources are some of the apparatus of Government, composed of the head of the village, the village Secretary, Financial Development, Kasie Kaur, and Kasie Kesra. Research done by disseminating a questionnaire in the form of a statement for the content and manner of doing observations about the financial management of the village. The results showed that for the planning and execution of the financial management of the village, already revealed the existence of a Village financial management accountable and transparent, but the Administration is still required the existence of a coaching more, because not yet fully comply with the provisions. The main obstacle is not yet effectively coaching apparatus of Government and the competence of human resources are adequate, so still need coaching and mentoring from BPMPD as local government authorities on an ongoing basis.